Fundamental frequency during cognitive preparation and its impact on therapy outcome for panic disorder with Agoraphobia. (December 2020) - Wieder, Gesine; Fischer, Melanie S.; Einsle, Franziska; Baucom, Donald H.; Hahlweg, Kurt; Wittchen, Hans-Ulrich; Weusthoff, Sarah
Abstract: Background: Cognitive preparation plays a crucial role in CBT with exposure for panic disorder and agoraphobia. High emotional arousal while developing the exposure rationale might impair patients' cognitive capacities for processing information about treatment and impede therapeutic outcome. Objective: This study investigates whether patients' vocally encoded emotional arousal, assessed by fundamental frequency (f0 ), during rationale development is associated with premature treatment dropout, insight into the rationale, and symptom reduction. Methods: Patients' ( N = 197, mean age 36.1 years, 79.2% female) f0 during rationale development was measured based on treatment videos from a randomized controlled trial of CBT for panic disorder and agoraphobia. Insight was rater assessed. Symptom severity was self- and rater assessed at the beginning and end of therapy. Results: Higher f0 mean during rationale development was associated with lower probability of insight and less reduction in avoidance behavior. f0 was not associated with dropout. Insight was associated with lower probability of dropout and partially mediated the association between f0 and avoidance reduction. Discussion: This study highlights the importance of emotional arousal during cognitive preparation for exposure. Therapists should ensure that patients are not too highly aroused while learning about the exposure rationale as an important step in treatment. Highlights: High arousal while developing the exposure rationale might affect therapy success. Emotional arousal can be non-intrusively assessed via fundamental frequency f0 . Higher patient f0 while developing the exposure rationale affects avoidance reduction. Rationale insight mediates the association between f0 and avoidance reduction. However, patient f0 is not associated with therapy termination.